The influence of international criminal law on refugee law - Rikhof, Joseph (Frontiers in Human Dynamics, 2023)
This article will discuss the relationship between International Criminal Law (ICL) and refugee law. The emphasis will be on the interplay between concepts developed in ICL with respect to war crimes and crimes against humanity, as well as the notion of extended liability on one hand and the exclusion provision in the 1951 Refugee Convention (Refugee Convention) on the other.